2011
DOI: 10.1007/s00330-011-2186-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive statistical iterative reconstruction versus filtered back projection in the same patient: 64 channel liver CT image quality and patient radiation dose

Abstract: Our initial results suggest low dose CT images reconstructed with ASIR may have lower measured noise, similar image quality, yet significantly less radiation dose compared with higher dose images reconstructed with FBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 11 publications
(26 reference statements)
4
60
1
Order By: Relevance
“…These include iterative reconstruction models such as adaptive statistical iterative reconstruction and model-based iterative reconstruction. [9][10][11][12][13][14][32][33][34][35][36][37][38][39][40] Although these imaging algorithms provide an additional method for dose reduction in CT-guided procedures, their availability is currently limited to newer CT scanners for routine diagnostic CT imaging. The greater availability of the iterative reconstruction software over time may allow for increased operator comfort when evaluating low-dose images during CT-guided procedures, potentially further reducing the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…These include iterative reconstruction models such as adaptive statistical iterative reconstruction and model-based iterative reconstruction. [9][10][11][12][13][14][32][33][34][35][36][37][38][39][40] Although these imaging algorithms provide an additional method for dose reduction in CT-guided procedures, their availability is currently limited to newer CT scanners for routine diagnostic CT imaging. The greater availability of the iterative reconstruction software over time may allow for increased operator comfort when evaluating low-dose images during CT-guided procedures, potentially further reducing the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…Increased image blurring has been discussed in several publications that investigated iterative reconstruction techniques. [11][12][13] Silva et al 12 suggested that the diminished noise manifests as an oversmoothing of the images. We have read with interest the results of Bulla et al, 8 who examined IRIS and concluded that iterative reconstructed paranasal sinus CT images did not lose image quality even though the tube current was reduced by Ͼ50%.…”
Section: Discussionmentioning
confidence: 99%
“…The application of such algorithms to images acquired with the Philips Brilliance Big Bore CT scanner has the potential to improve HU number accuracy and minimise the image artefacts seen at eFOV/sFOV, however deliberation of the aforementioned limitations should be considered. Alternately, the use of iterative reconstruction methods has been shown to be feasible to enhance image quality compared to FBP algorithms [16][17][18]. Although not assessed in this study the application of different iterative reconstruction algorithms may provide enhanced imaging accuracy within the eFOV region.…”
Section: Accuracy Of Spatial Data In Efov Regionmentioning
confidence: 90%